Adorno's Philosophy of New Music: A Thing of the Past?. Issue 1 (2nd January 2018) - Puolakka, Kalle
Abstract: Theodor W. Adorno (1903–1969) is a gigantic figure in musical aesthetics, and many still consider his views relevant, not only for analyzing the modernist music he was inspired by and that he inspired himself, but also for more contemporary developments in classical music. John Adams (b. 1947) is arguably the foremost contemporary composer who has tried to break away from the modernist musical language that was still very much dominant when he began his career as a composer, and he has been very outspoken about his antipathy toward the Schoenbergian-inspired compositional techniques that are at the background of Adorno's musical aesthetics, particularly his Philosophy of New Music . By presenting an interpretation of Adams' music that draws on some key aspects of John Dewey's aesthetics—aesthetic experience, rhythm, and his appreciation of common culture—I raise the question of how relevant Adorno's seminal book still is for understanding the aesthetics of the new music of today.